2004
DOI: 10.1002/hec.935
|View full text |Cite
|
Sign up to set email alerts
|

The sources of hospital cost variability

Abstract: Hospital heterogeneity is a major issue in defining a reimbursement system. If hospitals are heterogeneous, it is difficult to distinguish which part of the differences in costs is due to cost containment efforts and which part cannot be reduced, because it is due to other unobserved sources of hospital heterogeneity. In this paper, we apply an econometric approach to analyse hospital cost variability. We use a nested three-dimensional database (stays-hospitals-years) in order to explore the sources of variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…However, as there is clearly no unique cost per activity, an average cost is calculated although it is impossible to determine whether the mean is the Bcorrect value.'' The best solution should be a standard cost per DRG but various studies undertaken in France and elsewhere have showed the DRG cost variability [7,26,27]. According to a recent survey carried out by the General Inspector for Health and Social Action (IGAS) and the General Inspector for Finance (IGF) not only do hospitals have heterogeneous characteristics such as structure but patients' characteristics also differ.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, as there is clearly no unique cost per activity, an average cost is calculated although it is impossible to determine whether the mean is the Bcorrect value.'' The best solution should be a standard cost per DRG but various studies undertaken in France and elsewhere have showed the DRG cost variability [7,26,27]. According to a recent survey carried out by the General Inspector for Health and Social Action (IGAS) and the General Inspector for Finance (IGF) not only do hospitals have heterogeneous characteristics such as structure but patients' characteristics also differ.…”
Section: Discussionmentioning
confidence: 98%
“…There have been transition arrangements to allow the full implementation of the system [5]. Given the great diversity between hospitals [6,7] introducing the PPS suddenly would have had far too great an effect on the budgets, causing considerable increases or decreases of up to 30% in extreme cases [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus calculated, the estimated cost will evidently be all the higher that the hospital will be poorly efficient and that the demand, notably for a highly technical health care, will be low and conversely. The importance of the variation of the demand of health care in the determination of hospital costs is clearly pointed out by several studies (Macstravic, 1979(Macstravic, , 1981Carey, 1998;Baker et al, 2004;Dormont and Milcent, 2004). But the approach used in this paper establishes an initial assessment of costs by estimating the expenditures of the different hospital services and by relating them to their activity.…”
Section: Resultsmentioning
confidence: 96%
“…Further tests on the skewness and kurtosis of the distribution of hospitalisation costs in our sample revealed that these were closer to a lognormal than to a normal distribution. Thus, we used Log(Costs) as a dependent variable for the regression analysis (Dormont and Milcent, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Dormont and Milcent (2004) reported average total costs of h5978 per stay for AMI in France. Their calculations were based on 7314 cases documented in 36 French hospitals between 1994 and 1997.…”
Section: Discussionmentioning
confidence: 99%